Study and test of an active thermosiphon experimental set-up to validate Super-FRS dipoles cooling system. (April 2019) - Allain, H.; Baudouy, B.; Madur, A.; Rasamimanana, O.; Reymond, H.; Mueller, H.; Winkler, M.; Xiang, Y.; Wamers, F.; Cho, E. J.; Kauschke, M.
Abstract: In the framework of the Facility for Antiproton and Ion Research (FAIR) in Darmstadt, Germany, CEA is in charge of the design studies for superferric dipole magnets of the Superconducting Fragment Separator (Super-FRS). Each of these dipoles has 2 coils with a trapezoidal shape, each coil being cooled by a horizontal 20 × 10 mm 2 liquid helium channel (below or above the coil). The static heat load to extract is 5 W and, to generate a mass flow, the principle of a thermosiphon is implemented with a heater on the return pipe to force the flow direction of the thermosiphon. To validate this cooling system, an experimental set-up was designed and built at CEA Paris-Saclay. This paper presents the experimental set-up and the results of the tests. The effect of the horizontal heat load and the influence of the heater are reported.